2005
DOI: 10.1210/jc.2004-1216
|View full text |Cite
|
Sign up to set email alerts
|

Postprandial Plasma Ghrelin Is Suppressed Proportional to Meal Calorie Content in Normal-Weight But Not Obese Subjects

Abstract: Circulating levels of the gastric hormone ghrelin rise before and decrease after a meal. In normal-weight subjects, postprandial suppression of ghrelin is proportional to calories consumed. Obese individuals have lower fasting ghrelin levels; however, it is unclear whether the obese show normal postprandial suppression. This study aimed to compare postprandial ghrelin responses in normal-weight and obese subjects, using mixed macronutrient meals with varied fat and calorie content. Postprandial ghrelin respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
162
6
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(190 citation statements)
references
References 24 publications
17
162
6
5
Order By: Relevance
“…It has also been shown that the postprandial decline in ghrelin levels is less pronounced in obese compared to lean subjects (le Roux et al, 2005), and insulin resistance measured by euglycaemic hyperinsulinemic clamp was described inversely related to the insulininduced decrease in total serum ghrelin levels (Lucidi et al, 2002). This might explain the reduced decrease in postprandial total ghrelin response in insulin-resistant subjects as observed in the present study.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…It has also been shown that the postprandial decline in ghrelin levels is less pronounced in obese compared to lean subjects (le Roux et al, 2005), and insulin resistance measured by euglycaemic hyperinsulinemic clamp was described inversely related to the insulininduced decrease in total serum ghrelin levels (Lucidi et al, 2002). This might explain the reduced decrease in postprandial total ghrelin response in insulin-resistant subjects as observed in the present study.…”
Section: Discussionsupporting
confidence: 77%
“…Administration of acylated ghrelin to humans increased glucose levels and inhibited insulin secretion, whereas desacyl ghrelin antagonized these effects (Broglio et al, 2004). Postprandial ghrelin responses in humans might be proportional to caloric content and dependent on macronutrient intake (Callahan et al, 2004;le Roux et al, 2005). Little is known about the effects of dietary fibre intake on ghrelin secretion.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, reduced levels of ghrelin activity in obese individuals, as compared with non-obese controls, should provide greater protection from further weight gain. However, obese individuals display smaller post-prandial reductions in serum ghrelin levels, perhaps leading to a reduced feeling of satiety (Goldstone et al, 2005;le Roux et al, 2005). In an earlier study, food intake failed to suppress ghrelin levels in obese humans (English et al, 2002).…”
Section: Ghrelin and Obesitymentioning
confidence: 95%
“…Briefly the ghrelin radioimmunoassay was carried out as previously described. 17,18 The assay cross-reacted fully (100 %) with both acylated and des-acylated ghrelin associated with increases in plasma concentrations of 3 hormones involved in the appetite regulation. Specifically OSA patients have been reported to display elevated ghrelin, [11][12][13] leptin, 11 and neuropeptide Y (NPY).…”
Section: S C I E N T I F I C I N V E S T I G a T I O N Smentioning
confidence: 99%